2018
DOI: 10.1590/1414-431x20187813
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary angioedema with C1 inhibitor (C1-INH) deficit: the strength of recognition (51 cases)

Abstract: Hereditary angioedema (HAE) is a rare autosomal dominant disease due to C1 esterase inhibitor deficiency (C1-INH). The disease is characterized by subcutaneous and submucosal edema in the absence of urticaria due to the accumulation of bradykinin. This descriptive study aimed to evaluate the clinical characteristics of patients with a confirmed diagnosis of HAE referred to our Outpatient Clinic between December 2009 and November 2017. Fifty-one patients (38 F, 13 M) with a mean age of 32 years (range: 7–70 y) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
5
14
2
1
Order By: Relevance
“…FXII-HAE arises by a variant of FXII whereby Thr309 is substituted with a lysine or arginine (FXII-Lys/Arg309; 49 , 50 ). FXII Lys/Arg309 variants exhibit defective glycosylation which leads to a FXII structure that is more readily activated in the presence of a surface 51 , 52 . Recently N-glycosylation at Asn230 was identified 53 , offering an explanation for the low apparent molecular mass of FXII_∆KR mutant lacking that specific site.…”
Section: Discussionmentioning
confidence: 99%
“…FXII-HAE arises by a variant of FXII whereby Thr309 is substituted with a lysine or arginine (FXII-Lys/Arg309; 49 , 50 ). FXII Lys/Arg309 variants exhibit defective glycosylation which leads to a FXII structure that is more readily activated in the presence of a surface 51 , 52 . Recently N-glycosylation at Asn230 was identified 53 , offering an explanation for the low apparent molecular mass of FXII_∆KR mutant lacking that specific site.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the protective role of male hormones, as it was observed in other HAE patient study series [45]. Indeed, the high predominance of affected women may also be related to hormones, being the estrogens one of the main triggers of attacks in HAE [46,47]. However, we found that symptomatic females started to develop their symptoms sometime after the puberty period on average (25.4 ± 12.8 years), the period when most women affected by HAE debuts with symptoms.…”
Section: Discussionmentioning
confidence: 71%
“…It is worth noting that consumption of C4 happens even when patients do not have exposure to angioedema attacks. 8 Approximately 95% of HAE-C1INH patients show a reduced C4 level during remission and virtually 100% during an attack. 13 As HAE is a rare disease and the symptoms in the involved organ (for example, gastrointestinal tract) may resemble those of more common diseases (such as irritable bowel syndrome, small bowel obstruction, pancreatitis, or appendicitis), many patients with HAE may be underdiagnosed or misdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…In most epidemiological reports, type 1 and type 2 HAE, characterized by deficiency in C1–INH quantity and/or quality, account for the majority of the patients. 8 , 9 One study involving 137 Chinese HAE patients with C1–INH deficiency showed that type 1 HAE accounts for the majority (98.73%) of HAE patients and a minority (1.27%) of Chinese patients developed type 2 HAE. 10 Several SERPING1 gene mutations have been reported in Chinese HAE-C1INH patients.…”
Section: Introductionmentioning
confidence: 99%